The keystone of the Martin Luther’s (1483-1546) educational and pedagogical building - Padilla Caíña, Euclides (2018)
This article deals with the influence of the Protestant Reform in relation to pedagogy. Aspects such as the origins of the concept of “Christian freedom”, proposed by Luther, in jewish, early Christian and Rennaissance thought of philosophers such as Erasmus are aborded. The theological context of the Middle Ages and the critics towards it made by Luther’s pedagogical approach, based on the idea of “freedom”, are also analysed. The influence of the reformer on theology and philosophy is studied as well, leading to a reflexion on the different types of Christianity that have been brought to Latin America. In a continuous way, the work analyses the influence of Lutheran thought on the formation of Modernity.